Avaliação de níveis de pigmentos e crescimento da microalga Haematococcus pluvialis (Flotow 1844) cultivada em diferentes meios de cultura - SANTOS, Ana Paula Felipe dos (2016)
The Haematococcus pluvialis microalgae species is able to accumulate pigments (chlorophylls a and b, carotenoids –astaxanthin, β-carotene and lutein) with high value and commercial use when subjected to stress conditions, such as types of culture medium. The work aimed to study the growth of H. pluvialis and identify chlorophylls and carotenoids present in the cells, from the use of different culture medium. Six treatments were performed and different means were evaluated: Provasoli, Provasoli I modified, Provasoli II modified, KM1, MM2 and Guillard, all with three replications. The experimental units were conditioned in flasks with a volume of 2 liters, treated fresh water and enriched their culture medium. The microalgae were inoculated with an initial concentration of 1 x 105 cél.mL-1 and the treatments maintained at a temperature of 24 ± 1 ° C, photoperiod and light intensity integral 4000 lux. The assessment of growth, crop samples were taken and held daily counts by light microscopy. Growth curves were prepared for each treatment and the obtained values of the maximum cell density, culture time and the growth rate. For quantification of the pigments, samples of 2 ml were collected daily treatments, treated with 80% acetone in order to then be performed by reading the absorbance spectrophotometer. From the results of absorbances were calculated concentrations of chlorophyll a, chlorophyll b, total chlorophyll and total carotenoids. For data analysis was used Cochran, Shapiro-Wilk, ANOVA and Tukey test (P <0,05). The statistical results showed that there was significant difference (P <0,05) between treatments for maximum cell density, which was higher (21,42 ± 7,84 x 105 cél.mL-1) when using the medium Provasoli I modified, followed by Provasoli and Provasoli II modified means. Regarding pigments, significant differences (P <0,05) were observed for the concentration of chlorophyll b, total chlorophyll and total carotenoids, which were higher in the treatments used the Provasoli I modified, means Provasoli II modified and Provasoli. However, no significant differences were observed (P> 0,05) for chlorophyll a. For these experimental conditions suggest the use of the medium Provasoli I modified, so as to obtain a higher cell density and concentration of pigments of microalgae H. pluvialis.